Triterpenoid compound from metanol extract of mangrove leaves (Sonneratia alba) and anti-cholesterol activity test - Weny J.A Musa; Nurhayati Bialangi; Boima Situmeang; Saronom Silaban (Jurnal Pendidikan Kimia (JPKim), 2019)
Mangrove plant (Sonneratia alba) is easily found in West and North Indonesia. Mangrove plant has the potential of being a herb medicine. Mangrove plant variously used in ethnomedicine to treat various deseases like wounds, diarrhea, and fever. In previously sutudy, leaf extract of mangrove plants reported have anti-cholesterol activity. This plant is widely used to treat various deseases like wounds, diarrhea, and fever. The purpose of this study was to isolate triterpenoid compound from the ethyl acetate fraction of mangrove leaves and anticholesterol activity test. Extraction was done by maceration method using methanol 96% as solvent. Isolation was carried out by column chromatography using a combination of n-hexane, ethyl acetate, and methanol solvents. The elucidation of the structure was determined by analysis of IR, 1H-NMR, 13C-NMR, 2D-NMR, and MS spectroscopies as well as by comparisons with the literature. Anticholesterol activity test was carried out in vitro. The results showed that triterpenoid compounds (lupeol) were able to reduce cholesterol from concentrations of 5, 10, 20, 40, 60, and 80 ppm are 13.7; 29.4; 49.0; 60,1; 70.2; and 77.0% respectively. Therefore, isolates compound (lupeol) have anti-cholesterol activity.Keywords:Anti-cholesterol; mangrove; triterpenes